Non-symbiotic nitrogen fixation in tropical soils - Döbereiner, Johanna (Pesquisa Agropecuaria Brasileira, 2014)
The actual knowledge of non-symbiotic nitrogen fixation in tropical soils is compared with the situation of temperate regions where a contribution of economical importance to the N-economy of these soils has been-proved only under exceptional circumstances. The main differences of tropical soils seem to be the presence of at least six non-symbiotic nitrogen-fixing bacteria which have not been found in temperate soils and highly stimulating effects of certain grasses, the association of sugar cane with Beijerinckia spp. and that of Paspalum notatum with Azotobacter paspali being the most remarkable cases.